2013
DOI: 10.9710/kjm.2013.29.1.87
|View full text |Cite
|
Sign up to set email alerts
|

First record of Littorina (Littorina) kasaka (Littorinidae: Sorbeoconcha: Gastropoda) from Korea

Abstract: The Littorinid snail Littorina (Littorina) kasaka Reid, Zaslavskaya & Sergievsky, 1991, from Kandwon-do, Korea was recorded as new to the Korean molluscan fauna. Including the new recorded in this study, the family Littorinidae contained seven genera and 16 species in the Korean water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Based on morphological examinations of shell and radula morphology as well as molecular evidence, we conclude that a previous record identified as L. kasatka by Lee and Kil ( 2013 ) is likely to be a misidentification of L. sitkana . These two species can be often confused due to their nearly identical shell characters and broad within-species variation (Reid 1996 ).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Based on morphological examinations of shell and radula morphology as well as molecular evidence, we conclude that a previous record identified as L. kasatka by Lee and Kil ( 2013 ) is likely to be a misidentification of L. sitkana . These two species can be often confused due to their nearly identical shell characters and broad within-species variation (Reid 1996 ).…”
Section: Discussionmentioning
confidence: 72%
“…These two species can be often confused due to their nearly identical shell characters and broad within-species variation (Reid 1996 ). We found that the mtDNA cox1 sequence obtained from the sample that Lee and Kil ( 2013 ) used for their morphology-based identification of L. kasatka was nearly identical (up to 4 bp) to the cox1 sequence of L. sitkana on GenBank. Further morphological re-examination of Lee and Kil ( 2013 )’s specimens (identified by them as L. kasatka ) corresponds to the original description of the shell morphology of L. sitkana (Philippi 1846 ; Reid 1996 ).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations